Pembuatan Biodiesel Dari Biji Nyamplung Menggunakan Metode Tranesterifikasi Dengan Penambahan Toluena - Zulfikar Ainunsidiq, Mohammad; Huda, Miftakul; Ayu Titisari, Manik; Budi Pramana, Yanatra; Budipramana, Krisyanti (Universitas PGRI Adi Buana Surabaya, 2023)
The purpose of this study was to determine the effect of the addition of toluene on the quality of biodiesel from nyamplung seeds, including: viscosity, density, flash point. The method used is esterification using H2SO4 and then transesterification using NaOH. Biodiesel is then added to toluene. The ratio of the addition of toluene to the volume of biodiesel is 2%, 3%, 4% and 5% (%v/v). The final step is to analyze biodiesel which includes analysis of density, viscosity, and flash point. From this research, which gave the best results by adding 3% toluene, the density, viscosity and flash point values ​​met the standards of the Indonesian Biodiesel Forum. Namely a density value of 0,8415gr/ml, a viscosity of 4,7cSt, and a flash point of 62 °C.